Tingkat Pengetahuan Mahasiswa Prodi Manajemen Informasi Kesehatan tentang Penyakit Malaria - Bernad Julvian Zebua; Jetslin Simbolon; Selviani Damayanti Sipayung (Yayasan Literasi Sains Indonesia, 2024)
Malaria is a disease caused by parasites (protozoa) from the genus Plasmodium which live and reproduce in human red blood cells. This disease is naturally transmitted through the bite of female Anopheles mosquitoes. This study aims to determine the level of student knowledge about malaria in epidemiology courses. This research was conducted at STIKes Santa Elisabeth Medan in October using descriptive research methods. The population used was all level 1 and level 2 health information management study program students at STIKes Santa Elisabeth Medan with a sample size of 15 people. The instruments used were interviews and observations. The form of questionnaire used is a closed questionnaire, where the respondent chooses the correct answer according to the answer chosen in the research questionnaire. The research results showed that students with knowledge understood (73.7%) and did not understand (13.15%) it can be concluded that the level of knowledge of level I and II students of the Health Information Management study program knew about malaria in the epidemiology course, therefore students had to learn and understand and apply malaria prevention in epidemiology courses.